Inhibitory control and value-directed strategic attention in persons with mild age-related hearing loss - Shraddha A. Shende; Elizabeth A. Lydon; Fatima T. Husain; Raksha A. Mudar (Aging and Health Research, 2022)
Background: Growing evidence suggests changes in cognitive control in persons with age-related hearing loss (ARHL); however, the nature of these alterations especially in those with mild ARHL needs further investigation. Methods: This study examined group differences in cognitive control between 20 older adults with unaided mild ARHL and 20 age- and education-matched normal hearing (NH) controls using inhibitory control and value-directed strategic attention tasks. Additionally, the association between inhibitory control and strategic attention was evaluated. A visual Go/No-Go task and a value-directed word list learning task were used to examine inhibitory control and value-directed strategic attention, respectively. Results: Data analysis revealed that the persons with mild ARHL performed worse on both tasks relative to NH controls, suggesting poorer inhibitory control and lower value-directed strategic attention. Additionally, poorer inhibitory control was associated with worse strategic attention even when demographic variables, cognitive screening score, and hearing ability were controlled. Conclusions: Our findings contribute to the body of literature on modality-independent changes in cognitive control in persons with mild ARHL and advance our knowledge of the links between cognitive control processes.